Vitamin D supplementation for the treatment of COVID-19: A systematic review and meta-analysis of randomized controlled trials - Kümmel, Lara S.; Krumbein, Hanna; Fragkou, Paraskevi C.; Hünerbein, Ben L.; Reiter, Rieke; Papathanasiou, Konstantinos A.; Thölken, Clemens; Weiss, Scott T.; Renz, Harald; Skevaki, Chrysanthi (Frontiers in Immunology, 2022)
Vitamin D supplementation and its impact on immunoregulation is widely investigated. We aimed to assess the prevention and treatment efficiency of vitamin D supplementation in the context of COVID-19, and any disease-related complications. For this systematic review and meta-analysis, we searched databases (PubMed, Embase, Scopus, Web of Science, The Cochrane Library, medRxiv, Cochrane COVID-19 Study Register, and ClinicalTrial.gov) for studies published between November 1, 2019, and September 17, 2021. We considered randomized trials (RCTs) as potentially eligible, when patients were tested for SARS-CoV-2 infection, and received vitamin D supplementation, versus a placebo or standard of care control. Random-effects model was implemented to obtain pooled odds ratios for the effect of vitamin D supplementation on the main outcome mortality as well as clinical outcomes. We identified a total of 5733 articles, of which eight RCTs (657 patients) met the eligibility criteria. Although no statistically significant effects were reached, the use of vitamin D supplementation showed a trend for reduced mortality (odds ratio (OR) 0.74, 95% confidence interval (CI) 0.32–1.71, p=0.48) compared to the control group, with even stronger effects, when vitamin D was administered repeatedly (OR 0.33, 95% CI 0.1–1.14). The mean difference for length of hospitalization was -0.28 (95% CI -0.60–0.04), the OR for ICU admission 0.41 (95% CI 0.15–1.12) and for mechanical ventilation 0.52 (95% CI 0.27–1.02). In conclusion, vitamin D supplementation did not improve clinical outcomes in COVID-19 patients, but trends of beneficial effects were observed. Further investigations are required, especially studies focusing on daily administration of vitamin D.